Identification of the Genes Required for the Culture of Liberibacter crescens, the Closest Cultured Relative of the Liberibacter Plant Pathogens - Lai, Kin-Kwan; Davis-Richardson, Austin G.; Dias, Raquel; Triplett, Eric W. (Frontiers in Microbiology, 2016)
Here Tn5 random transposon mutagenesis was used to identify the essential elements for culturing Liberibacter crescens BT-1 that can serve as antimicrobial targets for the closely related pathogens of citrus, Candidatus Liberibacter asiaticus (Las) and tomato and potato, Candidatus Liberibacter solanacearum (Lso). In order to gain insight on the virulence, metabolism, and culturability of the pathogens within the genus Liberibacter, a mini-Tn5 transposon derivative system consisting of a gene specifying resistance to kanamycin, flanked by a 19-base-pair terminal repeat sequence of Tn5, was used for the genome-wide mutagenesis of L. crescens BT-1 and created an insertion mutant library. By analyzing the location of insertions using Sanger and Illumina Mi-Seq sequencing, 314 genes are proposed as essential for the culture of L. crescens BT-1 on BM-7 medium. Of those genes, 76 are not present in the uncultured Liberibacter pathogens and, as a result, suggest molecules necessary for the culturing these pathogens. Those molecules include the aromatic amino acids, several vitamins, histidine, cysteine, lipopolysaccharides, and fatty acids. In addition, the 238 essential genes of L. crescens in common with L. asiaticus are potential targets for the development of therapeutics against the disease.